Isolated congenital absent aortic valve cusps in a fetus: A case report - Sivanandam, S; Mackey-Bojack, S M (Indian Journal of Child Health, 2015)
Congenital absence of aortic valve cusps is an extremely rare congenital heart malformation. The absence of aortic valve cusps leads to severe aortic regurgitation with resultant rapid and progressive heart failure and growth retardation in the fetus. Congenital absence of the aortic leaflets in association with other cardiac defects has been reported in the literature, but the isolated anomaly is not reported yet. We present a case of a fetus with isolated congenital severe aortic regurgitation from absent aortic cusps and pathological specimen of this rare entity.